Materiais híbridos orgânico-inorgânicos siloxano-metacrilato como novos adsorventes para remoção do corante azul de metileno em meio aquoso - Sousa, Cássio Santos (2019)
Among the various dye removal processes in textile effluents, adsorption is considered one of the most effective and low cost. Thus, the present work evaluated the use of organic-inorganic siloxane-methacrylate hybrid materials obtained by the sol-gel process as adsorbent materials for the removal of methylene blue cationic dye in aqueous media. Three hybrid materials were synthesized: siloxane-poly (methyl methacrylate) (siloxane-pMMA), poly (methacryloxypropyltrimethoxysilane) siloxane (pMPTS) and siloxane-poly (hydroxyethyl methacrylate) (siloxane-pHEMA). The samples were characterized by elemental analysis (CHNO), Fourier Transform Infrared Absorption Spectroscopy (FTIR), nitrogen adsorption and desorption and determination of the zero-load pH (PZC) of the materials. The results of the characterization showed evidence of the formation of hybrids, which are mostly made up of mesoporous, and for pMPTS, a larger surface area, pore diameter and pore volume were observed. Dye removal capabilities were determined using the batch procedure. It was noted that there were more effective dye removals of the solutions, around 100%, when buffered dye solutions at pH 9 and sorption temperature of 50 °C were used. Sorption kinetic behavior presented good correlations for the pseudo-second order, Elovich and variable constants models, however, the variable constants model obtained better adjustments, obtaining lower standard deviation and chi-square values. The sorption mechanisms described by the intraparticle diffusion model suggest the rapid sorption caused by electrostatic attractions following a more gradual sorption caused by diffusion. In the reuse tests the hybrids were efficient, especially the pMPTS. The hybrid materials were very efficient and promising for the use of cationic dye removal in aqueous media.